Enhancing Numeracy Skills in Elementary Students through the Traditional Congklak Game: A Study in Kudus - Hariyadi, Ahmad; Rasyad, Afni; Rondhi S, Wawan; Santoso N, Denny; Najikhah, Fatikhatun (STAI Hubbulwathan Duri, 2024)
The objective of this study is to assess the efficacy of the conventional congklak game in enhancing numeracy abilities among primary school pupils in Kudus. The capacity to enumerate is a fundamental skill in the field of mathematics education, which is sometimes regarded as tedious by young learners. This study employed an experimental research approach and included a sample of 100 students representing diverse social and economic backgrounds. The employed methodologies encompass literature review, documentation, direct observation, and pre-test and post-test assessments to evaluate students' numeracy abilities. In addition, questionnaires and interviews were used to analyse several dimensions like learning motivation, social interaction, and family environmental support. The findings indicated that pupils who were taught utilizing the congklak game shown a notable enhancement in their numeracy abilities in comparison to students who employed traditional approaches, with an average rate of improvement of 28%. Furthermore, the congklak game has been empirically shown to enhance both learning motivation and social interaction among students. The findings of this study validate the need of including conventional games within the primary education curriculum in order to establish a learning environment that is both entertaining and efficient. Therefore, this study provides a substantial contribution to the advancement of novel and efficient learning methodologies. The findings from this study can serve as a valuable resource for policy makers and educators in developing a curriculum that is both engaging and effective in enhancing students' fundamental skills.